فاعلية استخدام استراتيجية الخرائط العقلية الالكترونية في اكساب مفاهيم تكنولوجيا التعليم لدى الطالبات المعلمات في كلية التربية في جامعة الاقصى بغزة - عبدالمنعم، رانية عبدالله محمد (جامعة الملك سعود - كلية التربية, 2015)
This study aimed to investigate the effectiveness of using electronic minds maps strategy and traditional methods in achieving some educational concepts among students' teachers at educational faculty in A1 Aqsa University in Gaza. The experimental design was used. Study sample consisted of (190) female students of the academic year 2013/2014, divided into two groups, control group (94) studied traditional method, and experimental group (96) studied by using the strategy of Mind Maps. The researcher used an educational material by using organized mind maps. Achievement test consisted of (30) multiple choices questions, Validity and reliability were insured. The results showed a statistical significant differences between post test control group and experimental group favor to experimental group, the effect size of the minds maps strategy was too large (r|2 =0.63), and Black gain rate was (1.32) this results could be attributed to the effectiveness of using the minds maps. The recommendation was to use mind maps in teaching methods in order to enable students to employ it in post graduation and during practice teaching.
هدفت الدراسة إلى استقصاء فاعلية استخدام استراتيجية الخرائط العقلية الإلكترونية في إكساب مفاهيم تكنولوجيا التعليم لدى الطالبات المعلمات في كلية التربية في جامعة الأقصى بغزة مقارنة بالطريقة التقليدية. استخدمت الباحثة المنهج التجريبي، وتكونت عينة الدراسة من (190) طالبة من طالبات كلية التربية بجامعة الأقصى للفصل الدراسي الأول من العام الدراسي 2013/2014، موزعين على مجوعتين؛ الأولى ضابطة (94) طالبة، درست بالطريقة التقليدية، والأخرى تجريبية (96) طالبة، درست باستخدام استراتيجية خرائط العقل. واستخدمت الباحثة في الدراسة مادة تعليمية منظمة باستخدام خرائط العقل، واختبار تحصيل لمفاهيم تكنولوجيا التعليم، كون من (30) فقرة من نوع الاختيار من متعدد. وتم التأكد من صدق الاختبار وثباته، وأظهرت النتائج وجود فرق ذي دلالة إحصائية بين مجموعتي الدراسة لصالح المجموعة التجريبية، وكان حجم تأثير استراتيجية خرائط العقل كبيرا جدا (0.63)، ومعامل الكسب لبلاك (1.32)، ويمكن أن تعزى هذه النتيجة إلى فاعلية استخدام الخرائط العقلية، وتوصي الدراسة بإدخال استراتيجية الخريطة العقلية ضمن مناهج طرائق التدريس في كلية التربية؛ لتدريب الطلبة على كيفية توظيفها بعد تخرجهم ومزاولتهم لمهنة التدريس.
711908
Keywords: تكنولوجيا التعليم -- طرق التدريس -- الطالبات المعلمات -- كليات التربية -- جامعة الاقصى -- اعداد المعلمين